Teachers' attitudes toward and frequency of engagement in reading aloud in the primary classroom - Merga, Margaret; Ledger, S. (WILEY-BLACKWELL, 2018)
© 2018 UKLA Reading aloud to children is considered one of the most highly effective strategies for fostering a range of literacy skills, both at home and within contemporary classrooms. However, little is known about teachers' attitudes toward reading aloud, their self-reported frequency of engagement in the practice and what may pose as contemporary barriers to the practice. The 2016 Western Australian Study in Reading Aloud (WASRA) collected data from over 100 teachers at 14 Australian schools. The WASRA reveals tensions in translating reading aloud practices into daily practice due to reported lack of time and high curriculum demands. The findings suggest that primary school teachers typically enjoy reading aloud to children, though fewer enjoyed reading themselves. Recommendations are provided to address time and curriculum demands purported as being inhibitors of daily reading practices. These recommendations go some way to help mitigate against literacy inequities within our primary classrooms and in so doing encourage provision of daily reading opportunities for teachers and reading aloud practices.